Coronary artery ectasia associated with IgG4-related disease: a case report and literature review - Muyun Tang; Zhiyu Zhang; Liang Wang; Hao Qian; Wei Wu; Zhenyu Liu; Zhujun Shen; Hua Chen; Zhiwei Guo; Ran Tian; Shuyang Zhang (BMC Cardiovascular Disorders, 2023)
Abstract Background Coronary artery ectasia is defined as a local or diffuse dilatation of the coronary artery more than 1.5 times the diameter of the adjacent normal segment. The etiology of coronary artery ectasia is diverse, and rarely complicated with immunoglobulin G4-related disease (IgG4-related disease). A limited number of cases have been reported, with insidious onset, slow progression but poor prognosis. Case presentation we report a patient with coronary artery ectasia combined with IgG4-related disease. He has been diagnosed with IgG4-related disease 5 years after his first percutaneous coronary intervention (PCI). Despite routine treatment with steroids, he develops a large coronary aneurysm and eventually died. Conclusions It is suggested that a thorough evaluation should be performed when coronary artery ectasia is diagnosed. The factors such as manifestations of coronary artery thickening, typical imaging features, other aortas involvement, increased serum IgG4 level, etc. should be considered for early diagnosis of key etiologies.